Theoretical quantification for cracks repair based on microbially induced carbonate precipitation (MICP) method. (April 2021) - Sun, Xiaohao; Miao, Linchang; Wu, Linyu; Wang, Hengxing
Abstract: Concrete cracks have an adverse impact on the durability and safety of the concrete structures; and thus, repairing cracks to improve their mechanical properties is of great significance. Recently, microbially induced carbonate precipitation (MICP) has been extensively studied to repair concrete cracks; however, few studies focused on the theoretical quantitively model to study the repair effects of MICP. In this study, a theoretical calculation model with MICP was obtained by considering transport of solute, transport of suspended biomass, biofilm growth, geochemistry, ureolysis, and calcium carbonate (CaCO3 ) precipitation. Moreover, the feasibility and practicability of the mathematical model were demonstrated by the crack repair tests. The results showed that the calculated concentrations of suspended biomass in cracks gradually decreased during the tests; and the concentrations were larger for larger cracks. The comparison between the calculated results and experimental results demonstrated the correctness of transport mode of suspended biomass. The volume fractions of biofilm and solute concentrations were larger at the inlet, resulting in the increase of productive rates for CaCO3, which were consistent with experimental results. For smaller cracks, the consumed concentrations of solutes were larger, eventually leading to smaller sonic time values; and the upper parts of cracks had smaller sonic time values, indicating better repair effects. The proposed mathematical model represents a platform technology that leverages microbial metabolism and repair period to impart novel adjustive, sensing, biomineralization, and bioremediation multifunctionality to structural materials, which would lay a solid foundation for material remediation in civil engineering and material engineering fields.